Izucenie otnošenija k probleme dopinga sportivnych žurnalistov, rukovoditelej sportivnych federacij/associacij i predstavitelej regional'nych organov ispolnitel'noj vlasti v sfere fiziceskoj kul'tury i sporta - Derevoedov, A. A.; Zorenko, A. V.; Brus, E. V.; Zagorskiy, I. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Article considers attitudes towards doping of sport federations leaders, regional government officials and sport journalists as a group of experts. A qualitative survey as a part of sociological research using semi-structured interview method by phone was carried out for the sake of determining expert attitude. Expert opinion and attitude towards doping problem and different aspects of anti-doping work were obtained as a result of the aforementioned research.